Agriculture, Diversification, and Gender in Rural Africa : longitudinal perspectives from six countries - Andersson Djurfeldt, Agnes, 1973-; Dzanku, Fred M.; Isinika, Aida C., 1951- (Oxford University Press, 2018)
This book contributes to the understanding of smallholder agriculture in sub-Saharan Africa through addressing the dynamics of intensification and diversification within and outside agriculture in contexts where women have much poorer access to agrarian resources than men.